Market Strategi Entry (Studi kasus PT. Aquarium Shrimp) - Rizal, Nanda Amyrul; Simanjorang, Ramayanti; Dalimunte, Rodiah; Mazruk, Sherina Said; Suhairi, Suhairi (Jurnal Manajemen Akuntansi (JUMSI), 2021)
Research on export strategy conducted by PT. Aquarium shrimp in entering the global market shows that the company is in Quadrant I is supporting the strategy of SO (Strengths-Opportunities) by using existing strengths to take advantage of opportunities. As for the other three strategies such as St (Strengths–Threats),WT(weaknesses–Threats)and wo (Weaknesses–Opportunities) Strategies are supporting strategies. The company's export strategy has been an aggressive strategy, including market penetration, market development and product development. As for the employees who were selected to be respondents as many as 20 people to fill in the closed and 5 people to be interviewed,where among them are people who are influential in making decisions on the export strategy. This is done to see the export strategy carried out by the company is in an aggressive, conservative, defensive or Competitive Strategy.